2016 Production Status and Market Prospect of Eco-Friendly Agricultural Products at Home and Abroad - 정학균 (한국농촌경제연구원, 2016)
○ The cultivation area of environmentally friendly agricultural products (organic and non-pesticide) has declined since 2013, but is expected to grow again after 2016. - As the requirements for certification of eco-friendly agricultural products were tightened due to the credibility issues, the cultivation area of these products has reduced by an annual average of 16.1% since 2013. - However, it is expected to increase again after 2016 in case the 4th Five-Year Plan for the Development of Environmentally Friendly Agriculture, aimed at improving the certification system, expanding the distribution system, facilitating consumption and reinforcing the production infrastructure, is implemented well as planned. ○ The market size of eco-friendly agricultural products has also reduced due to the decrease in the number of certification cases. The market is estimated to be worth KRW 1.2718 trillion as of 2015, an 18.8% decline from the previous year. - The market of environment-friendly agricultural products shrank in 2015 because the reduction in the area of farmland with eco-friendly certification led to the decrease in the volume of shipment. - Among various commodities in the market, fruits take up 8.0%, which is very little compared to grains (42.8%) and vegetables (21.7%). ○ Thanks to the global trend of well-being, the size of the organic agri-food market has gradually increased since 2000 mainly in advanced countries, including the US and European countries. - As of 2014, organic agricultural products are produced in 43.66 million ha of farmland in about 172 countries around the world, and the volume is on the steady increase. - The scale of the global organic agri-food market rapidly grew from USD 15 billion in 1990 to USD 64 billion in 2012 (an increase by 4.3 times) and to USD 80 billion in 2014 (an increase by 5.3 times). ○ The market for eco-friendly agricultural products is expected to grow again from 2016 with the fostering policies of the government. - The implementation of the 4th Five-Year Plan for the Development of Environmentally Friendly Agriculture starting from 2016 is predicted to lead to a steady growth of the market size, presumably reaching KRW 2.5242 trillion by 2020 and KRW 3.9862 trillion by 2025. ○ It is crucial to make efforts based on policies to facilitate the stable supply and consumption of environment-friendly agricultural products. - In the short term, for a smooth supply of eco-friendly fruits in response to the abolition of the certification system for low-pesticide agricultural products, it is needed to come up with measures for enhancing the direct payment system, introducing the insurance system for producers, and designing and disseminating the cultivation manuals for organic fruits. - In the medium and long term, it is necessary to expand the industrial foundation for eco-friendly processed food and the domestic and overseas markets in relation to the food service industry and export, thereby responding to the expansion of the market for environment-friendly agricultural products.